National Geographic kids almanac 2024. - National Geographic Partners (U.S.) (Washington, D.C. National Geographic, 2023)
"Brings you incredible photos, amazing animals, extreme adventures, fascinating facts, and tons of fun!"--Back cover.
Your world 2024 -- Kids vs. plastic -- Amazing animals -- Space and Earth -- Awesome exploration -- Fun and games -- Laugh out loud -- Culture connection -- Science and technology -- Wonders of nature -- History happens -- Geography rocks.
Includes bibliographical references (page 355) and index.
Keywords: Almanacs, American -- Juvenile literature; Almanacs, Children's -- Juvenile literature; Curiosities and wonders -- Juvenile literature; Almanacs; Curiosities and wonders